Downregulation of miR‐638 promotes invasion and proliferation by regulating SOX2 and induces EMT in NSCLC. Issue 14 (17th May 2014) - Xia, Yang; Wu, Yanhu; Liu, Bin; Wang, Pengli; Chen, Yijiang
Abstract : Aberrant expression of microRNAs has been shown to regulate the biological processes of lung cancer cells. However, the role of miR‐638 in the development of NSCLC is still unclear. In this study, low miR‐638 and high SOX2 were shown to be associated with tumor size and metastasis of NSCLC patients. Downregulated miR‐638 could promote cell invasion and proliferation, while high miR‐638 expression reversed the effect. Furthermore, miR‐638 could regulate SOX2 by directly binding to its 3′‐UTR. Silencing of SOX2 by siRNA partially abolished the enhancement of cell invasion and proliferation induced by downregulated miR‐638. Aberrant miR‐638 expression could modulate the expression levels of markers of epithelial‐to‐mesenchymal transition. Our results indicate that miR‐638 may play a pivotal role in the development of NSCLC. Abstract : Expression of miR‐638 is reduced in lung cancer tissues. Downregulation of miR‐638 is related to the invasion and proliferation of lung cancer cell lines. Direct binding of miR‐638 to the SOX2 3′‐UTR is confirmed. miR‐638 overexpression diminishes but miR‐638 knockdown increases SOX2 expression levels in vitro. Aberrant expression of miR‐638 is related to invasion and proliferation of NSCLC by regulating SOX2.